Analisis Dampak Pemasangan ATCS Terhadap Emisi Gas Buang (CO2) di Jl. Jend. Sudirman Kota Tangerang - Jatmiko, Wahyu (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
In its effort to reduce congestion, Tangerang City Government has installed ATCS in several priority intersections using green wave concept (coordinated green light in priority intersections to reduce delay). The study investigated the change in CO2 emission in relation to the installation of ATCS on Jl. Jend Sudirman road section through traffic performance examination (of delay and travel time). Analysis showed that the installation of ATCS in the study area has improved the traffic performance, indicated by the reduction of average delay as much as 5,633 seconds (23,03%), increase in average speed as much as 1,56 km/hour (5,347%), reduction of average CO2 emission (15,26% at static and 6,208% while moving), therefore saving fuel consumption. In this study, delay has been identified as the variable having the greatest impact in the reduction of CO2 emission. This study argues that as positive results have been observable, the employment of ATCS for priority intersections optimization may be extended.